25(OH)D Concentration in Neonates, Infants, and Toddlers From Poland—Evaluation of Trends During Years 1981–2011 - Wójcik, Marek; Jaworski, Maciej; Pludowski, Pawel (Frontiers in Endocrinology, 2018)
Introduction: The numerous evidence showing spectrum of vitamin D effects on human health resulted in both updates of vitamin D supplementation guidelines for general population and concerns on potential risk of hypercalcaemia. The aim of this study was to analyse trends in serum 25-hydroxyvitamin D concentration (25(OH)D) change over the 30 years of operation of a single pediatric diagnostic unit. Materials and methods: Calcium-phosphate metabolism markers and 25(OH)D concentrations were analyzed in a group that consisted of newborns and infants commissioned for diagnostics due to suspected calcium-phosphate metabolic disturbances (n = 3,163; mean age 8.0 ± 3.0 months). Results: 25(OH)D < 10 ng/ml was noted in 4.5% of patients (n = 163), 10–20 ng/ml in 14.7% (n = 465), 20–30 ng/ml in 23.9% (n = 756) and 30–50 ng/ml in 35.9% (n = 1,136). The mean 25(OH)D concentration in analyzed group was 37.5 ± 24.5 ng/ml. In patients with 25(OH)D concentration < 10 ng/ml a normal calcaemia (2.25–2.65 mmol/l) was noted in 83.4% cases (n = 136). Eighty one patients had 25(OH)D concentrations above 100 ng/ml with co-existing calcaemia in range of 2.6–4.38 mmol/l (mean Ca = 2.69 mmol/l). Hypocalcaemia (Ca < 2.25 mmol/l) was observed in 0.54%, (n = 17). 13.8% patients revealed calcium levels >2.65 mmol/l (n = 435). In general, the mean calcium-phosphate markers values were within the reference range for age. The highest mean 25(OH)D concentration of 51.8 ng/ml ± 38.8 was noted in years 1981–1999 (n = 305). The lowest mean 25(OH)D value was observed in years 2010–2011 (29.0 ng/ml ± 13.6; n = 412). The trend of decreasing 25(OH)D concentration during analyzed time period was significant (r = −0.29, p < 0.0001). Conclusions: Eighty percentage of children aged 0–36 months had 25(OH)D concentration >20 ng/ml, however, during 3 decades a mean 25(OH)D concentrations trended significantly to decrease. A direct relationship between low 25(OH)D concentration and hypocalcaemia was not observed nor between high 25(OH)D concentration and hypercalcemia.